Factors Associated With Hearing Loss Among Patients At Hearing Clinic X In Surabaya City - Hesti Zulviyah Al Mumtazah; Dwi Faqihatus Syarifah Has (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Introduction: Hearing loss is a health problem that can affect communication skills, social interactions, quality of life, and individual productivity. The incidence of hearing loss is influenced by various factors, such as genetic factors, noise exposure, ototoxic factors, and certain medical conditions. This study aims to analyze the relationship between genetic factors, noise exposure, ototoxic and medical factors with hearing loss in patients at Hearing Clinic X in Surabaya City. Methods: This study is an observational analytical study with a cross-sectional design. The sample consisted of 67 respondents selected using a simple random sampling technique. Data were collected through a World Health Organization (WHO) questionnaire, the Noise Exposure Questionnaire (NEQ), and hearing test results. Data analysis was performed univariately and bivariately using the Chi-square test at a significance level of 5%. Results and Discussion: A total of 27 respondents (40.3%) had hearing loss and 40 respondents (59.7%) had normal hearing. The results of the Chi-Square test showed that genetic factors (p=0.008), noise factors (p=0.003), and ototoxic and medical factors (p<0.001) were significantly associated with hearing loss. Ototoxic and medical factors showed the strongest association, with 81.3% of respondents in the at-risk group experiencing hearing loss. Conclusion: Genetic factors, noise factors, and ototoxic and medical factors were significantly associated with hearing loss in patients at Hearing Clinic X in Surabaya City. Increasing education, early detection, controlling noise exposure, and monitoring the use of ototoxic drugs and comorbidities are needed to prevent hearing loss.